Difusión de la danza contemporánea a través de los audiovisuales en la ciudad de Quito - Pozo Quinteros, Edgar Javier (2015)
Dance and communication are important resources that complement each other to generate knowledge and welfare in society development. Along time, communication reached to establish itself as a human being necessity. That constant desire of transmitting information, ideas and emotions is based on theory that professionals on this area have explored to define patterns and classify specific communicative attributes like mass communication. Internet is a necessary element for people‟s daily life and for art diffusion. Websites and social media are useful platforms that reach global population, generating opinion and information to society. This media could represent a resource for incentivize artistic content at local and international level. This project is specially focused on audiovisual communication on Internet and located on national and international contemporary dance research field. It comprehends history facts, important exponents and cultural background that have been useful as base for the impulse of this dance genre. In consequence, the look goes to precedents, personalities and progress of Ecuadorian dance from the view of Quito‟s institutions and the transmission of artistic contents that exists nowadays on audiovisual media and the stage. It looks forward to understand and know about city‟s current art to create a new communicative product known as dance-video, which will allow to transmit in a creative, convenient and massive way, contemporary dance for the citizens. The development of this project pretends to give way to broadcast new kinds of expression from audiovisual artists and those who belong to the world of the dance.